BANTUAN HIDUP DASAR (BHD) DI SMA N 3 BATANG HARI - Tri Andini, Febri; Erwinsyah; Riama, Apni; Anipah, Anipah (STIKES Garuda Putih, 2025)
Background: Emergencies can occur to anyone, at any time and in any place. An emergency is a condition that requires immediate and appropriate action; failure to respond promptly may result in death. Basic Life Support (BLS) is an emergency procedure aimed at clearing the airway, assisting breathing, and maintaining blood circulation without the use of medical equipment. Objective: The BLS training activity aims to enhance students' knowledge in providing first aid during emergency situations. Method: The target of this study was 46 students of Grade XII at SMA Negeri 3 Batanghari. The methods used included lectures, discussions, and demonstrations. Results: The BLS training provided students of Grade XII at SMA Negeri 3 Batanghari with information about choking and appropriate handling techniques. Conclusion: The implementation of BLS training at SMA Negeri 3 Batanghari is a crucial step in improving students' knowledge and skills in emergency response and management. Key Word ; Basic life support, emergency, choked